2012
DOI: 10.1038/onc.2012.179
|View full text |Cite
|
Sign up to set email alerts
|

The MUC4 mucin mediates gemcitabine resistance of human pancreatic cancer cells via the Concentrative Nucleoside Transporter family

Abstract: The fluorinated analog of deoxycytidine, Gemcitabine (Gemzar), is the main chemotherapeutic drug in pancreatic cancer, but survival remains weak mainly because of the high resistance of tumors to the drug. Recent works have shown that the mucin MUC4 may confer an advantage to pancreatic tumor cells by modifying their susceptibility to drugs. However, the cellular mechanism(s) responsible for this MUC4-mediated resistance is unknown. The aim of this work was to identify the cellular mechanisms responsible for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 44 publications
4
128
2
1
Order By: Relevance
“…The need for a more-effective pancreatic cancer treatment strategy is urgent and the link between DUSP28 and MUC5B and MUC16 expression may enhance understanding of the development of malignant pancreatic cancer. MUC16 has been reported previously to be a key factor in pancreatic cancer malignancy [27,28]. However, we suggest the importance of MUC5B in pancreatic cancer cells for the first time and that MUC5B and MUC16 are involved more closely in human pancreatic cancer malignancy than previously recognized.…”
Section: Introductioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The need for a more-effective pancreatic cancer treatment strategy is urgent and the link between DUSP28 and MUC5B and MUC16 expression may enhance understanding of the development of malignant pancreatic cancer. MUC16 has been reported previously to be a key factor in pancreatic cancer malignancy [27,28]. However, we suggest the importance of MUC5B in pancreatic cancer cells for the first time and that MUC5B and MUC16 are involved more closely in human pancreatic cancer malignancy than previously recognized.…”
Section: Introductioncontrasting
confidence: 46%
“…Several studies have suggested that mucins regulate the ERK1/2, p38, mTOR and c-Myc intracellular signalling pathways in pancreatic cancer cells. The regulation of MUC5B and MUC16 expression by DUSP28 therefore might affect various MAPK signalling pathways [15,27,28]. Silencing of MUC5B and MUC16 caused reduction of phospho-ERK1/2 levels compared with those of phospho-FAK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic and biologic data show a clear association between chronic inflammatory conditions and subsequent malignant transformation (31). Colorectal cancer is an inflammatory bowel disease (32), and several studies showed that JNK signaling is critical for pancreatic cancer development (33,34). Recently, many dietary compounds have been recognized as potential anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al that contribute to gemcitabine resistance include NF-κB, 114 heat shock proteins, and the presence of highly resistant tumor stem cells.…”
mentioning
confidence: 99%